2020
DOI: 10.1186/s12872-020-01408-1
|View full text |Cite
|
Sign up to set email alerts
|

Features of serum fatty acids in acute ischaemic stroke patients aged 50 years or older

Abstract: Background: Serum fatty acid (s-FA) compositions and their correlation with serum lipids (s-LPs) such as total cholesterol (T-CHO) and triglycerides (TG) have been reported in healthy young subjects. However, little is known about such features in acute ischaemic stroke (AIS). The aim of our study was to investigate s-FA characteristics and their correlation with AIS in elderly patients. Methods: We conducted a cross-sectional study of patients aged 50 years or older who were admitted between September 2015 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The bioactive form of lipoxin A4-15-epi-lipoxin A 4 (15-epi LXA 4 ) that promotes resolution of inflammation by inhibiting superoxide generation and polymorphonuclear leukocyte transmigration was found to be higher in embolic when compared to undetermined subtype of stroke [ 78 ]. It was observed that higher levels of SFA and n6 PUFA were associated with lacunar and atherosclerotic stroke, while no relationships regarding the n3 DHA and the subtypes of stroke were observed [ 79 , 80 ]. Higher levels of C14:0 myristic acid were identified in small-vessel subtypes of stroke in comparison to large-vessel and embolic ones, but in other SFAs (C15:0 pentadecanoid acid) its level was lower in small-vessel compared to undetermined type.…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive form of lipoxin A4-15-epi-lipoxin A 4 (15-epi LXA 4 ) that promotes resolution of inflammation by inhibiting superoxide generation and polymorphonuclear leukocyte transmigration was found to be higher in embolic when compared to undetermined subtype of stroke [ 78 ]. It was observed that higher levels of SFA and n6 PUFA were associated with lacunar and atherosclerotic stroke, while no relationships regarding the n3 DHA and the subtypes of stroke were observed [ 79 , 80 ]. Higher levels of C14:0 myristic acid were identified in small-vessel subtypes of stroke in comparison to large-vessel and embolic ones, but in other SFAs (C15:0 pentadecanoid acid) its level was lower in small-vessel compared to undetermined type.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that there is a direct connection between the risk of an ischemic stroke and an individual’s metabolic and physiological status. Furthermore, the serum concentration levels of the Omega 6:Omega 3 ratio is a significant indicator of physiological dysfunction and the onset of insulin resistance in stroke survivors [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between serum FA levels under fasting conditions and stroke has been reported [8][9][10]. However, few studies have reported on serum FA levels at the onset of ischemic events [11,12], which are typically examined under non-fasting conditions and associated with the dietary intake of TGs. Higher intake of seafood may be associated with higher n-3 PUFA levels, which is likely to reduce the risk of ischemic events.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the wt % values of EPA and DHA are lower in subjects with CAD than in healthy controls [15]. Interestingly, in patients who experienced lacunar or atherosclerotic stroke between the ages of 50-74 years, the serum concentrations of saturated fatty acids (SFAs), n-9 monounsaturated fatty acid (n-9 MUFA), and n-6 PUFAs are elevated [11,12]. This suggests that the serum concentrations and wt % of FAs are related to the age of acute ischemic disease onset.…”
Section: Introductionmentioning
confidence: 99%